Changes in the spatial and temporal population density of the Medditerranean fruit fly (Diptera: Tephritidae) in a citrus orchard - Alemany, A.=700 1 Miranda, M.A.; Alonso, R.; Martin Escorzaa, C.
(Es, En)
ilus., 22 ref.
Keywords: CITRUS; CERATITIS CAPITATA; CONTROL DE PLAGAS; DISTRIBUCION GEOGRAFICA; ESPAÑA; KRIGING